The Impact of Operational Scenarios and Concrete Aging Factor on the Freeboard Height of an Irrigation Canal - Kazem, Masoud; Nazari-Sharabian, Mohammad; Afzalimehr, Hossein; Darban, Nader; Karakouzian, Moses (Engineering, Technology & Applied Science Research, 2023)
The prediction of operational freeboard in irrigation canals is a complicated issue, particularly when the cumulative effects of time-dependent factors, such as maloperation and concrete aging, are considered. While most classic approaches consider a fixed freeboard due to uniform flow as a fundamental assumption. Τhis study proposes a flowchart considering the effects of nonuniform flow to determine the adequacy of the freeboard of irrigation canals under different conditions, including time-dependent and operational scenarios. The results of this method indicated that the freeboard values obtained by classical methods may not be sufficiently reliable in providing the appropriate level of performance in the operating conditions of agricultural canals. Regarding the case study of this paper, an irrigation canal in Kurdistan-Iran, the results showed that the formation of the M1 profile is the most critical scenario and the initial freeboard must be extended by 20cm at a distance of about 2.3Km at the end of the canal towards upstream.